Histomorphological Characteristics of Digestive and Reproductive Organs of Lutzomyia wellcomei Fraiha, Shaw & Lainson (Diptera, Psychodidae) - Pegado Silva, Vanessa Escóssia; da Silva, Naissandra Bezerra; Pinheiro, Marcos Paulo Gomes; Freitas, Maria de Lourdes; Freire de Melo Ximenes, Maria de Fátima (EntomoBrasilis, 2013)
Sandflies are important vectors of tegumentary and visceral leishmaniasis in different countries. This study aimed at analyzing the histomorphological characteristics of digestive and reproductive organs in Lutzomyia wellcomei (Fraiha, Shaw & Lainson) using light microscopy techniques. Thirty females from the rural area of Nísia Floresta, Rio Grande do Norte state were selected, microsectioned and analyzed with an optical microscope using conventional hematoxylin-eosin staining. Results show three well-characterized regions in the digestive tube: the stomodeum, mesentery and proctodeum. The stomodeum is lined internally with a basal and epithelial membrane; the mesentery has a peritrophic matrix formed above the stomodeum lining consisting of the simple cubic epithelium overlapping the conjunctive, also common to a capsule of gonadal lining; and the proctodeum, which structurally resembles the mesentery, but with a pyloric sphincter limiting the posterior midgut. Enveloping the digestive tube is the peritoneal membrane, of mesodermal origin. Richly-detailed internal morphological characteristics of L. wellcomei have widened knowledge of this Leishmania braziliensis (Vianna)-transmitting species, an etiologic agent of American tegumentary leishmaniasis. Características Histomorfológicas de Órgãos da Digestão de Lutzomyia wellcomei Fraiha, Shaw & Lainson (Diptera, Psychodidae) Resumo. Os flebotomíneos se destacam como importantes transmissores das leishmanioses tegumentar e visceral em diferentes países. O objetivo desse estudo foi analisar características histomorfológicas de órgãos da digestão de Lutzomyia wellcomei (Fraiha, Shaw & Lainson) por meio de técnicas de microscopia. Trinta fêmeas provenientes de área rural do município de Nísia Floresta, Rio Grande do Norte foram selecionadas, microseccionadas e analisadas por microscopia ótica. Métodos de coloração histológica por hematoxilina-eosina foram empregados nas análises. Os resultados mostram o trato digestório com as três regiões bem caracterizadas, estomodeo, mesêntero e proctodeo. O estomodeo possui uma membrana basal e uma membrana epitelial que o reveste internamente; o mesêntero possui matriz peritrófica formada acima do revestimento do estomodeo constituído de epitélio cúbico simples sobreposto ao conjuntivo comum também a uma cápsula de revestimento gonadal; e o proctodeo que se assemelha estruturalmente com o mesêntero, possuindo ainda, uma região pilórica limitando o intestino médio do posterior. Envolvendo o tubo digestório, está a membrana peritonial, de origem mesodérmica. As características morfológicas internas, observadas com riqueza de detalhes em L. wellcomei ampliam o conhecimento acerca dessa espécie, transmissora de Leishmania braziliensis (Vianna), agente etiológico de leishmaniose tegumentar americana.